Air kerma area product in cone beam computed tomography - de Oliveira, Marcus Vinicius Linhares; Batista, Wilson Otto Gomes; Soares, Maria Rosângela; Campos, Paulo Sergio Flores (Revista de Ciências Médicas e Biológicas, 2014)
Objective: to evaluate the influence of FOV in air kerma-area product (KAP) and the constancy of exposure parameters on cone beam computed tomography equipments. Methodology: Two cone beam CT (GENDEX CBX 500 and i-CAT Classic) were used and seven exposures with the following FOVs were performed: (A) 14cm x 8,5cm, (B) 14cm x 6cm, (C) 8,5cm x 8.5cm e (D) 8,5cm x 6cm, for CBX 500; and (E) 14cm x 6.cm, (F) 14cm x 8cm e (G) 14cm x 13cm, for the i-CAT. The technical exposure factors (kV, mA, mAs and voxel), remained constant. The dosimetric evaluation was performed with air KAP meter manufactured by IBA dosimetry, model kerma X plus TinO, positioned at the output of the X-ray beam. To evaluate the constancy of the exposure parameters a semiconductor (Radcal, Rapidose) fixed in front of the tomography image receptor was used. Result: The KAP values ​​obtained ranged between 360.1 mGy.cm² and 1031.2 mGy.cm². The FOV height had a substantial influence on the radiation dose. Repeatability and accuracy of the tube voltage varied less than 10%. Conclusion: The radiation dose is directly related to the height and inversely related with the FOV diameter; even within the recommended limits, the percentage variation of repeatability and accuracy of kV, for the tomography equipments tested, points to the regular equipment calibration, in order to reduce radiation dose to the patient to a minimum.